Development of a predictive model for detection of Mycobacterium avium subsp. paratuberculosis in faeces by quantitative real time PCR - Kralik, Petr; Slana, Iva; Kralova, Alena; Babak, Vladimir; Whitlock, Robert H; Pavlik, Ivo (Veterinary microbiology, 2011)
This study focused on the development of a reliable and cost-efficient DNA isolation procedure for the detection of Mycobacterium avium subsp. paratuberculosis (MAP) in faeces by previously developed IS900 and F57 quantitative real time PCR (qPCR) and their comparison with culture. The recovery of MAP DNA from the spiking experiments ranged from 29.1 to 102.4% of the input amount of MAP with median 37.9%. The limit of detection was determined to be 1.03 × 10(4) for F57 qPCR and 6.87 × 10(2)MAP cells per gram of faeces for IS900 qPCR, respectively. The developed technique for DNA isolation was coupled with IS900 qPCR and compared to traditional MAP culture using a cohort of 1906 faecal samples examined from 12 dairy cattle farms in our laboratory. From those 1906 original faecal samples, 875 were positive by IS900 qPCR and 169 by culture. None of the culture positive samples was negative by IS900 qPCR. This data facilitated development of a predictive model capable of estimating the probability of being culture positive by estimating the absolute number of MAP per gram of faeces as determined IS900 qPCR without performing the culture.
Keywords: Limit of Detection; nemoci skotu; limita detekce; logistické modely; DNA bakterií; senzitivita a specificita; Sensitivity and Specificity; feces; Paratuberculosis; Mycobacterium avium subsp. paratuberculosis; zvířata; Feces; DNA, Bacterial; paratuberkulóza; Cattle; Cattle Diseases; polymerázová řetězová reakce; skot; Polymerase Chain Reaction; Animals; Logistic Models